Peritoneopericardial diaphragmatic hernia in the dog and cat - NIKIPHOROU, X.; CHIOTI, R.; PATSIKAS, M. N.; PAPAZOGLOU, L. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Peritoneopericardial diaphragmatic hernia (PPDH) is a congenital communication between the pericardial sac and the abdominal cavity allowing displacement of abdominal organs to the pericardial sac. Peritoneopericardial diaphragmatic hernia is thought to occur due to a failure of the development of septum transversum. Vomiting, exercise intolerance and respiratory distress are the most common clinical signs. Diagnosis of PPDH is based on plain radiography. Physical examination and diagnostic imaging may detect the presence of other congenital anomalies. Surgical repair of the PPDH is the treatment of choice for animals with clinical signs. Prognosis following surgical repair of PPDH is favorable. Animals with no clinical signs related to PPDH may not undergo surgical repair.